Aspectos de la heterogeneidad espacial en relación a la dinámica poblacional de Nezara viridula (L.) (Hemiptera: pentatomidae) - Liljesthröm, Gerardo Gustavo (1988)
The density of two Nezara viridula adult populations was estimated taking into account the occurrence in different plant communities situated in cultivated areas, which were described considering their species composition and structure. The study site includes two sampling places, both located at the "area Platense", Province of Buenos Aires, Argentina. The two sampled populations shaw four adult generations during their active life cycle; the last recorded being, the pre-reproductive one. Hibernation starts at the beginning of fall, and activation reinitiates at early. spring, when N. viridula selectively colonizes plant communities of definitive species composition and structure.